Örgütsel desteğin yenilikçi iş davranışına etkisinde psikolojik güçlendirmenin düzenleyici rolü : sağlık sektöründe çalışanlar üzerine bir araştırma - Akbulut, Feyza Nur (My University, 2025)
Bu araştırmanın temel amacı, sağlık sektöründe örgütsel desteğin yenilikçi iş davranışı üzerindeki etkisini ve psikolojik güçlendirmenin bu ilişki üzerindeki düzenleyici rolünü incelemektir. Araştırmada nicel yöntem kullanılarak Türkiye sağlık sektöründe farklı görevlerde çalışan 291 kişiden anket yoluyla veriler toplanmıştır. Doğrusal regresyon analizi sonucunda örgütsel desteğin yenilikçi iş davranışı üzerinde anlamlı ve pozitif bir etkisi olduğu bulunmuştur. Ayrıca psikolojik güçlendirmenin yenilikçi iş davranışı üzerinde güçlü ve pozitif bir doğrudan etkisi olduğu ve örgütsel destek ile yenilikçi iş davranışı arasındaki ilişkiyi negatif yönde düzenlediği tespit edilmiştir. Bu sonuçlar, örgütsel desteğin çalışanların yenilikçi davranışlarını teşvik ettiğini, psikolojik güçlendirmenin ise çalışanların içsel motivasyonunu artırarak yenilikçi davranışları üzerinde kritik bir rol oynadığını ortaya koymaktadır. Bulgular ışığında, sağlık sektöründeki yöneticilere çalışanların yenilikçilik potansiyellerini artırmak için örgütsel destek ve psikolojik güçlendirme uygulamalarına ağırlık vermeleri önerilmektedir. Gelecekte farklı sektör ve örneklemler üzerinde benzer çalışmalar yapılması tavsiye edilmektedir.

This study aims to examine the effect of perceived organizational support on innovative work behavior among employees working in the healthcare sector and to evaluate the moderating role of psychological empowerment in this relationship. The research hypothesizes that organizational support positively influences innovative work behavior. A quantitative research approach was employed, and data were collected via structured questionnaires administered to 291 employees across various healthcare institutions in Turkey. Data analysis was performed using linear regression. The findings revealed that perceived organizational support significantly and positively influences employees' innovative work behavior. Furthermore, psychological empowerment also exhibited a strong and positive direct effect on innovative work behavior. Interestingly, psychological empowerment was found to moderate the relationship between perceived organizational support and innovative work behavior negatively, indicating that as the level of psychological empowerment increases, the direct impact of organizational support on innovative work behavior diminishes. These results underscore the importance of fostering organizational support mechanisms and psychological empowerment practices to stimulate innovation within the healthcare sector. The study provides practical implications for healthcare administrators seeking to enhance employee-driven innovation by integrating organizational support and empowerment strategies effectively. Future studies are encouraged to explore similar relationships across different sectors and contexts.
The moderating role of psychological empowerment in the effect of organizational support on innovative work behavior : a study on employees in the healthcare sector
Keywords: Creative ability in business; innovative work behavior; Management; Medical personnel; Organizational change; Organizational support; Örgütsel değişim; Örgütsel destek; psikolojik güçlendirme; psychological empowerment; Sağlık personeli; Turkey; Türkiye; Yaratıcılık yeteneği, İşletmelerde; yenilikçi iş davranışı; Yönetim